2021
DOI: 10.3390/biology10080780
|View full text |Cite
|
Sign up to set email alerts
|

Is the Life History Flexibility of Cold Desert Annuals Broad Enough to Cope with Predicted Climate Change? The Case of Erodium oxyrhinchum in Central Asia

Abstract: Interannual seasonal variability in precipitation may strongly affect the life history and growth of desert annual plants. We compared the effects of dry and wet springs and dry and wet autumns on growth and F2 seed dormancy of plants from spring (SG)- and autumn (AG)-germinated seeds of the cold desert annual Erodium oxyrhinchum. Vegetative and reproductive growth and F2 seed dormancy and germination were monitored from September 2016 to November 2020 in the sandy Gurbantunggut Desert in NW China in Central A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…In this study, the plant height of A. linifolium (Figure 2) decreased significantly under the drought treatment, and all plants showed varying degrees of reduction in aboveground biomass accumulation (Figure 4). Similar results were found in related studies, in which ephemeral plants showed significantly lower height and biomass in a dry spring than in a wet spring [41]. Drought stress may cause stomatal closure and decreased enzyme activity, which may limit the photosynthetic capacity of plants and reduce the accumulation of dry matter.…”
Section: Effect Of Precipitation Changes On Ephemeral Plantssupporting
confidence: 89%
“…In this study, the plant height of A. linifolium (Figure 2) decreased significantly under the drought treatment, and all plants showed varying degrees of reduction in aboveground biomass accumulation (Figure 4). Similar results were found in related studies, in which ephemeral plants showed significantly lower height and biomass in a dry spring than in a wet spring [41]. Drought stress may cause stomatal closure and decreased enzyme activity, which may limit the photosynthetic capacity of plants and reduce the accumulation of dry matter.…”
Section: Effect Of Precipitation Changes On Ephemeral Plantssupporting
confidence: 89%
“…In this paper, E. oxyrhinchum was selected to investigate the effects of drought treatment on its PSII activity. At present, some researchers have studied the effects of precipitation on the isochronous germination of E. oxyrhinchum (Liu et al, 2021), the influences of snow on its seedling growth (Wu et al, 2018), and the impacts of water and nitrogen additions on its life history (Chen et al, 2019). In terms of photosynthesis, the impacts of precipitation on chlorophyll fluorescence (Zhang et al, 2022) and the influences of biological soil crusts on photosynthetic characteristics (Zhuang and Zhang, 2017) are the only topics that have been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change not only significantly affects the land mass of the arid zone but also significantly impacts plant growth and distribution—for example, climate change has effects across multiple plant life stages, seed germination ( Mondoni et al., 2012 ), seedling establishment ( Footitt et al., 2018 ), vegetative growth ( Li et al., 2020 ; Zhao et al., 2021 ), reproductive development ( Hacket-Pain & Bogdziewicz, 2021 ), and seed dispersal ( Hamaoui-Laguel et al., 2015 ) as well as distribution ( Bellard et al., 2012 ; Hu et al., 2015 ; Liu et al., 2021 ). Recently, ecologists recognized species distribution as a common focus of interest because it is the basis for understanding the mechanisms of species formation, evolution, and adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Plants have adapted to their environment over long periods and, under specific conditions, have formed a unique group of ephemeral plants. Ephemeral plants are life forms found in dry winter-wet steppes, deserts, and Mediterranean grasslands or areas with a short favorable season ( Louise & Bliss, 1982 ; Liu et al., 2021 ). Vegetative and reproductive growth quickly takes advantage of optimal conditions, such as temperature, moisture, and sunlight, etc .…”
Section: Introductionmentioning
confidence: 99%